The pricing kernel puzzle: A behavioral explanation - Hammad Siddiqi; John C. Quiggin (Cogent Economics & Finance, 2019)
We show that if sophisticated institutional managers and individual investors perceive tail-risks differently, then a new explanation for the pricing kernel puzzle emerges. We show, by example, that even a tiny difference in tail-risk perception by the two investor types can explain the pricing kernel puzzle.
Keywords: D00; D40; G12; G13; 330; Differential awareness; pricing kernel puzzle; rare disasters